1993
DOI: 10.1111/j.1469-8749.1993.tb07921.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Spastic Cerebral Palsy—a Comparative Study Between Southwest Germany and Western Sweden. I: Clinical Patterns and Disabilities

Abstract: SUMMARY The results of a collaborative study of bilateral spastic cerebral palsy (BSCP) between south‐west Germany and western Sweden are reported, comprising 249 children in south‐west Germany and 264 children in western Sweden. A severe gross motor disability was present in 65 per cent of the German and 62 per cent of the Swedish children; learning difficulties or mental retardation in 73 and 76 per cent; active epilepsy in 28 and 26 per cent; and severe visual disability in 20 and 19 per cent, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
27
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 15 publications
7
27
1
3
Order By: Relevance
“…The traditional clinical terminology used to describe the subtypes of CP has been confusing (Ingram 1984), and the standard form for describing children with a central motor deficit is an attempt to avoid these terms (Evans et al 1989). A similar but more precise approach was used in the collaborative work done by groups in Göteborg and Tübingen (Krageloh-Mann et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The traditional clinical terminology used to describe the subtypes of CP has been confusing (Ingram 1984), and the standard form for describing children with a central motor deficit is an attempt to avoid these terms (Evans et al 1989). A similar but more precise approach was used in the collaborative work done by groups in Göteborg and Tübingen (Krageloh-Mann et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…22 Because the 2 pathologies have similar etiologies and are associated with spastic diparesis and leg-dominant quadriparesis, they continue to be combined under the umbrella term of periventricular leukomalacia. 23 Two of the previously reported series of patients with cerebral palsy and periventricular leukomalacia [1][2][3][4][5][6][7][8][9] have included cohorts with periventricular leukomalacia detected through routine imaging studies of the whole cerebral palsy population. Carlsson et al 6 identified 34 subjects with periventricular leukomalacia from a population base of 600 000; it is not clear from their report whether any of their cohort had any other radiologic findings.…”
Section: Discussionmentioning
confidence: 99%
“…7,9 Epilepsy occurs in most individuals with large cortical lesions, whether unilateral or bilateral, pathologies usually associated with arm-dominant quadriparesis or hemiparesis. 1,11,12 Although less common, epilepsy is nevertheless a significant complication for children with periventricular leukomalacia, with reported incidence figures of 16.0% to 47%. 6,9,13 The main patterns of cerebral palsy in children with periventricular leukomalacia are spastic diparesis and This article reports an analysis of risk factors for epilepsy in children with radiologically confirmed periventricular leukomalacia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14 The Surveillance of Cerebral Palsy in Europe (SCPE) has therefore decided to use a simplified classification for spastic children of uni-or bilateral CP. 15,16 The SCPE has also developed a reference manual with a hierarchal diagnostic tree for CP and its subtypes, 16 which offers relatively good reliability (kappa 0.63; Surman G, personal communication 2003). Moreover, the SCPE constructed the concept of 'severe CP' by combining severe motor disability, i.e.…”
mentioning
confidence: 99%